Search for neutrino emission from gamma-ray flaring blazars with the ANTARES telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Astroparticle Physics, 2012)
The ANTARES telescope is well-suited to detect neutrinos produced in astrophysical transient sources as it can observe a full hemisphere of the sky at all times with a high duty cycle. Radio-loud active galactic nuclei with jets pointing almost directly towards the observer, the so-called blazars, are particularly attractive potential neutrino point sources. The all-sky monitor LAT on board the Fermi satellite probes the variability of any given gamma-ray bright blazar in the sky on time scales of hours to months. Assuming hadronic models, a strong correlation between the gamma-ray and the neutrino fluxes is expected. Selecting a narrow time window on the assumed neutrino production period can significantly reduce the background.An unbinned method based on the minimization of a likelihood ratio was applied to a subsample of data collected in 2008 (61 days live time). By searching for neutrinos during the high state periods of the AGN light curve, the sensitivity to these sources was improved by about a factor of two with respect to a standard time-integrated point source search. First results on the search for neutrinos associated with ten bright and variable Fermi sources are presented. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino astronomy; Fermi LAT transient sources; Time-dependent search; Blazars